Penggunaan Media Sosal sebagai Media Komunikasi dalam Penyebaran Informasi pada Dinas Kominfo Kota Medan - Razak, Abdul; Sumanti, Solihah Titin (Medan Resource Center, 2023)
The emergence of social media has had a significant impact on the way people communicate. This applies not only to individuals but also to government organizations. Most local governments in Indonesia have yet to harness the presence of social media as a means of communication. The objective of this research is to identify the use of social media as a communication medium in the dissemination of information and the barriers to information dissemination from the Office of Communication and Information Services (Kominfo) in the city of Medan. This study utilizes a qualitative descriptive method. Interviews, observations, or in-depth documentation are used as data collection approaches. The snowball sampling method is employed to identify informants. Data triangulation is used to examine the accuracy of the data, with the hope of reducing potential inaccuracies. The main components of the interactive data analysis approach used in this study are data reduction, data display, conclusion drawing, and verification. The output of this study is the utilization of social media by the Office of Communication and Information Services (Kominfo) in the city of Medan as a communication tool.